(No) laughing allowed — humour and the limits of soft power in prison - Laursen, Julie (The British journal of criminology, 2017)
Although humour in prison is a widespread phenomenon, its meaning and function has not been examined in any detail. This article seeks to address this gap by analysing humour in prison-based cognitive behavioural programmes. The empirical data from fieldwork in three different programme settings illuminate how the participants actively disrupt and twist the power hierarchies by providing a kind of humorous meta-commentary on the simplicity and class bias of the course content. This article suggests that humour could be seen as a tool that enables prisoners to fend off the psychological and rhetorical power of the cognitive behavioural programmes, even if only briefly. By developing the concept of ‘soft resistance’ and analysing humour as friction and code-switching, this article aims to illustrate and discuss the limits of soft power in prison-based therapeutic settings.